What Do Workers Want? Attitudes Towards Collective Bargaining and Participation in Management - Richards, John; Mauser, Gary; Holmes, Richard (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
This article analizes an exploratory survey, conducted in Vancouver, on public attitudes towards industrial democracy.